Beginning ASP.NET for Visual Studio 2015 - Penberthy, William (Wrox, a Wiley brand, 2016)
Beginning ASP.NET for Visual Studio 2015 is your ultimate guide to the latest upgrade of this historically popular framework. Fully updated to align with the vNext release, this new edition walks you through the new tools and features that make your workflow smoother and your applications stronger. You'll get up to speed on the productivity and performance improvements, and learn how Microsoft has committed itself to more continuous innovation by increasing its release cadence for all products and services going forward. Coverage includes Async-aware debugging, ADO.NET idle connection resiliency, managed return value inspection, ASP.NET app suspension, on-demand large object heap compaction, multi-core JIT and more.